Use of Artificial Intelligence in Human Resource Management - Supriyadi, Supriyadi; Firmansyah Y.A, Firmansyah Y.A (International Journal of Artificial Intelligence Research, 2024)
The abstract must be between 150–250 words. Be sure that you adhereto these limits; otherwise, you will need to edit your abstractaccordingly. The abstract must be written as one paragraph, and shouldnot contain displayed mathematical equations or tabular. The use ofartificial intelligence (AI) in human resource management (HRM) isgaining increasing attention, with many organizations recognizing itspotential to enhance operational efficiency. The majority of respondentsin this study demonstrate awareness of AI, with more than halfunderstanding the technology and its functions in the context of HRM.Most respondents hold a positive view towards AI adoption, with over60% believing that AI can improve organizational efficiency. Keybenefits identified include time savings in recruitment, improved dataanalytics, and more accurate employee turnover predictions. However,despite the widespread support for AI, some concerns remain. About12% of respondents expressed concerns regarding algorithmic bias thatmay arise in AI-driven decision-making processes, as well as challengesin safeguarding employee privacy. These issues highlight theimportance of caution when implementing AI, ensuring that thetechnology does not exacerbate inequalities or infringe upon individualprivacy. Overall, the survey results reflect a generally positive attitudetowards AI, while also emphasizing the need for a more cautiousapproach in its application. Organizations must address ethical andprivacy concerns and ensure that AI is used to support fair andtransparent decision-making